Aisyiyah Organization Communication Network In Tuberculosis Prevention In North Sumatra - Kholil, Syukur; Yusnadi, Yusnadi; Tambunan, Nurhalima (Faculty of Law, Universitas Pekalongan, 2024)
The purpose of this study was to analyze the communication network built by the Aisyiyah organization in the prevention of Tuberculosis (TB) in North Sumatra. Aisyiyah as Lembaga autonomy Muhammmadiyah who became one of the government fatners in the eradication of tuberculosis. Eradication of tuberculosis is something that must be done in breaking the chain of the spread of tuberculosis that is of concern to the world because the disease is very fast spreading and is the no. 2 deadly disease after HIV Aids. Transmission is through people infected with tuberculosis coughing and removing mycobacterium bacteria. The research methods used are descriptive through qualitative approaches. The informant in this study was the Head of Aisyiyah Region of North Sumatra, TB-HIV Care Aisyiyah Team of North Sumatra. Data collection techniques through interviews, observations, and documentation. The results showed that the communication network built by Aisyiyah North Sumatra in the prevention of Tuberculosis by forming TB-HIV Care Aisyiyah. Cadres as implementers who plunge into the community to the village level in helping to provide services in collaboration with puskesmas services. Cadres in carrying out this humanitarian task always put forward human values by not paying attention to race, religion, or ethnicity. For cadres to be able to carry out tasks in the field are given debriefing that supports competence in the form of knowledge related to TB, effective communication and evaluation, and reporting, in addition, cadres in performing their duties are provided facilities such as jackets of pinaster marks, participant cards as TB cadres. . As for the reporting made by cadres so that sufferers, suspects more easily obtain drug services that can later be obtained from the nearest health center whose treatment is provided by the government for free. The recruitment of these cadres is usually done through Aisyiyah studies or can be done through other channels such as through social media, and in coordination with other organizations or associations such as the PKK Mother